PENGARUH PENYULUHAN KESEHATAN TENTANG GASTRITIS TERHADAP PENGETAHUAN DAN PERILAKU PENCEGAHAN PADA SANTRI PP. AN-NASHRIYAH BAHRUL ‘ULUM TAMBAKBERAS JOMBANG - Bagus, Nanang; Firdaus, M. Hanif; Roni, Faishol (WELL BEING, 2018)
Gastritis is an inflammation of the gastric mucosa that occurs due to lack of keeping diet, smoking, drinking coffee, eating spicy and sour. The incidence of healthy behavior starts from a good knowledge and obtained from the extension of health, so that health counseling needed in an environment of boarding schools in order that students behave in a healthy life. The purpose of this study was to analyze the influence of health education on knowledge and behaviour against gastritis prevention on students. Design research using Pre Experimental approach One Group Pre Test – Post Test Design. The sample of this research are all students PP. An-Nashriyah Bahrul ‘Ulum Tambakberas Jombang is 54 respondents using the total population. The data collected by using questionnaire and given health counselling before and after. Analysing ways is to use the wilcoxon test with a significance level of p ≤ 0.05. The results showed that there was influence of knowledge before and after the given health counselling about gastritis with significance p = 0.000. Likewise there are also preventive behavior influence with their significance was p = 0.002. This means that there are influences between health counselling about gastritis to knowledge and behavior of prevention. With the research community is expected to find out ways to prevent the occurrence of gastritis.